2020
DOI: 10.33235/wpr.28.1.30-37
|View full text |Cite
|
Sign up to set email alerts
|

Use of iodine-impregnated surgical drapes for prevention of surgical site infection: a systematic review and meta-analysis

Abstract: For referencing Nicholson O et al. Use of iodine-impregnated surgical drapes for prevention of surgical site infection: a systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A previous review reported the intervention had no effect on the SSI rate compared to no drape (RR 1.03, 95% CI 0.06 to 1.66, p = 0.89) ( WHO 2018 ). A review by Nicholson et al (2020) found iodine-impregnated drapes are beneficial in reducing postoperative SSI for all surgeries including clean-contaminated and contaminated surgeries. Recent UK guidelines recommend the use of an iodophor-impregnated drape if a plastic adhesive drape is required unless there are any contraindications such as iodine allergy ( NICE 2020 : p9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous review reported the intervention had no effect on the SSI rate compared to no drape (RR 1.03, 95% CI 0.06 to 1.66, p = 0.89) ( WHO 2018 ). A review by Nicholson et al (2020) found iodine-impregnated drapes are beneficial in reducing postoperative SSI for all surgeries including clean-contaminated and contaminated surgeries. Recent UK guidelines recommend the use of an iodophor-impregnated drape if a plastic adhesive drape is required unless there are any contraindications such as iodine allergy ( NICE 2020 : p9).…”
Section: Discussionmentioning
confidence: 99%
“…However, searches using the terms ‘iodine-impregnated incise drape,’ ‘ioban’ and ‘surgical site infection’ in PubMed on 22 July 2021 found no additional relevant publications. The Nicholson et al (2020) review was identified subsequently but did not identify new studies meeting our inclusion criteria.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations